1985
DOI: 10.1111/j.1365-2125.1985.tb02605.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dazoxiben, an inhibitor of thromboxane synthetase, on cold‐induced forearm vasoconstriction and platelet behaviour in different individuals.

Abstract: 1 The effect of dazoxiben, a thromboxane synthetase inhibitor, on cold-induced forearm vasoconstriction was determined in two groups of human volunteers, those in whom dazoxiben abolished the platelet aggregation and release reaction induced by sodium arachidonate (group I) and those in whom it did not (group II). Dazoxiben abolished cold-induced forearm vasoconstriction in group I volunteers but not in those of group II. These results imply a correlation between platelet behaviour and cold-induced changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Using forearm and finger venous occlusion plethysmography, previous research has demonstrated that the reflex vascular responses to arm or foot cooling are not altered by COX inhibition (Cowley et al 1983(Cowley et al , 1985Gresele et al 1985;Hechtman & Jageneau, 1985), with one study demonstrating an increase in vascular resistance during foot cooling (Serneri et al 1981). As the skin temperature (in degrees Celsius; B) during hand cooling and subsequent spontaneous rewarming after placebo and COX inhibition * Significant difference (P < 0.05) between CAU and AFD after placebo.…”
Section: Placebo Cox Inhibitionmentioning
confidence: 99%
“…Using forearm and finger venous occlusion plethysmography, previous research has demonstrated that the reflex vascular responses to arm or foot cooling are not altered by COX inhibition (Cowley et al 1983(Cowley et al , 1985Gresele et al 1985;Hechtman & Jageneau, 1985), with one study demonstrating an increase in vascular resistance during foot cooling (Serneri et al 1981). As the skin temperature (in degrees Celsius; B) during hand cooling and subsequent spontaneous rewarming after placebo and COX inhibition * Significant difference (P < 0.05) between CAU and AFD after placebo.…”
Section: Placebo Cox Inhibitionmentioning
confidence: 99%